American way of life : representação e consumo de um estilo de vida modelar no cinema norte-americano dos anos 1950 - Cunha, Paulo Roberto Ferreira da (2017)
This thesis aims to understand the context and the articulations related to the consumption of model images of a lifestyle pattern – named as American way of life –, through the dissemination of mass communication, in particular, of North American cinema in the 1950‟s. Such mediatization of images made sense to viewers and adhered to the common sense of United States citizens. However, in parallel with the pedagogical action of the diffusion of said model, contradictions and contextual factors that did not conform to pattern and which continued to be presented in that society – as well as in the films – have dialogued with diverse portions of the population and have generated verisimilitude to the referenced displayed on the screen. In this way, after the film analysis of production launched in the aforementioned decade, this project will have a responsibility to understand the process, the elements, the strategies and the plural representations implemented by film industry in order to include in the films features of the model and non-model – after all, making sense is a way of working on the order to of customer loyalty. The research carried out through the contemporaneousness of the theme is justified, since a significant part of the cultural and media production of the United States in the 20th century crossed frontiers and reached the world, taking with it the image of a country and of exemplary citizens whose form of living should be a reference – as it still is in certain instances.